Genetics of Venous Thrombosis: update in 2015 - Morange, Pierre-Emmanuel; Suchon, Pierre; Trégouët, David-Alexandre (Thrombosis and Haemostasis, 2015)
Venous thrombosis (VT) is a common multifactorial disease with a genetic component that was first suspected nearly 60 years ago. In this review, we document the genetic determinants of the disease, and update recent findings delivered by the application of high-throughput genotyping and sequencing technologies. To date, 17 genes have been robustly demonstrated to harbour genetic variations associated with VT risk: ABO, F2, F5, F9, F11, FGG, GP6, KNG1, PROC, PROCR, PROS1, SERPINC1, SLC44A2, STXBP5, THBD, TSPAN15 and VWF. The common polymorphisms are estimated to account only for a modest part (~5 %) of the VT heritability. Much remains to be done to fully disentangle the exact genetic (and epigenetic) architecture of the disease. A large suite of powerful tools and research strategies can be deployed on the large collections of patients that have already been assembled (and additional are ongoing).
Keywords: Venous thrombosis; single nucleotide polymorphisms; gene mutations